Program Rohis DKM Al-Ma’wa di SMAN 1 Cianjur dalam Meningkatkan Sikap Sosial Anggota Rohis di SMAN 1 Cianjur - Zainal Mutaqien; Ikin Asikin; Nurul Afrianti (Bandung Conference Series: Islamic Education, 2022)
Abstract. This study aims to determine: (1). The program carried out by the management of ROHIS DKM Al-Mawa at SMAN 1 Cianjur in improving social attitudes. (2). social attitudes of spiritual members towards SMAN 1 Cianjur in improving social attitudes. (3). The role of administrators and members of ROHIS DKM Al-Mawa at SMAN 1 Cianjur towards other students in improving social attitudes. This research is a quantitative research located at SMA Negeri 1 Cianjur in Cianjur regency. Data collection uses two methods, namely questionnaires and documentation. The method used is the survey method, namely by collecting research data information with samples that are analyzed from population data. While the approach used is quantitative. All data were analyzed using a quantitative approach and descriptive statistical analysis, namely by using product moment correlation analysis techniques and t tests which were then analyzed by simple regression analysis to test the proposed hypothesis. The results of this study indicate that 1). The influence of the program carried out by the management of ROHIS DKM Al-Mawa at SMAN 1 Cianjur in improving social attitudes. (2). There is an influence of social attitudes of spiritual members towards SMAN 1 Cianjur in improving social attitudes. (3). There is an influence of the role of administrators and members of ROHIS DKM Al-Mawa at SMAN 1 Cianjur on other students in improving social attitudes. Keywords: Influence, Spiritual Program, Mosque Prosperity Council And Social Attitude. Abstrak. Penelitian ini bertujuan untuk mengetahui: (1).Program yang dilakukan oleh pengurus ROHIS DKM Al-Mawa di SMAN 1 Cianjur dalam meningkatkan sikap sosial. (2).sikap sosial anggota rohis terhadap di SMAN 1 Cianjur dalam meningkatkan sikap sosial. (3). Peranan pengurus dan anggota ROHIS DKM Al-Mawa di SMAN 1 Cianjur terhadap siswa lain dalam meningkatakan sikap sosial. Peneltian ini merupakan penelitan kuantitatif yang berlokasi di SMA Negeri 1 Cianjur di kabupatern Cianjur. Pengumpulan data menggunakan dua metode yaitu angket dan dokumentasi. metode yang digunakan metode survei yaitu dengan cara mengumpulkan informasi data penlitian beru sampel yang dianalisis dari data populasi. Sedangkan Pendekatan yang digunakan kuantitatif. Keseluruhan data dianalisis mengunakan pendekatan kuantitatif dan analisis statistic deskriptif yaitu dengan menggunakan teknik analisis korelasi product moment dan uji t yang kemudian di analisis dengananalisis regresi sederhana untuk menguji hipotesis yang telah diajukan. Hasil Penelitian ini menunjukan bahwa diperoleh terdapat 1). Pengaruh Program yang dilakukan oleh pengurus ROHIS DKM Al-Mawa di SMAN 1 Cianjur dalam meningkatkan sikap sosial. (2).Terdapat pengaruh sikap sosial anggota rohis terhadap di SMAN 1 Cianjur dalam meningkatkan sikap sosial. (3). Terdapat pengaruh peranan pengurus dan anggota ROHIS DKM Al-Mawa di SMAN 1 Cianjur terhadap siswa lain dalam meningkatakan sikap sosial.